Sovereign debt crisis : the new normal and the newly poor - Chorafas, Dimitris N. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
This book focuses on sovereign debt, sovereign risk and the developing economic and financial business climate and explains why the year of the big crisis may fall in the middle of this decade.
Includes bibliographical references and index.
oif 11/06/15
Loan
Keywords: Debts, External; Debt relief; Financial crises; Economic stabilization